Nordic Walking Improves Postural Alignment and Leads to a More Normal Gait Pattern Following 8 Weeks of Training in Older Adults - Dalton, Christopher (Université d'Ottawa / University of Ottawa, 2016)
Background: Declines in gait velocity, stride length, cadence, and postural stability are common with advancing age and have further been linked to heightened fall risk and functional decline. Physical activity can slow or prevent such gait declines in older adults. In young adults, Nordic walking (NW) training has been shown to increase stride length and gait speed, yet has demonstrated inconsistent findings regarding joint loading, with reports of both increases and decreases in this respect. Further, research of this facet has very minimally been examined as it pertains to older adults. Purpose: The aim of the present study was to determine both the initial effect, and the prolonged effect following an 8-week intervention, of Nordic walking (NW) on older adult gait performance and postural alignment and stability. Methods: Gait and postural alignment and stability during NW and conventional walking were assessed and compared following an 8-week NW program (2x/week) in 12 healthy older adults (age: 68 ± 6.8 years; 8 female, 4 male). Participants performed six 5m walking trials, 3 with poles and 3 without, followed by two 6 Minute Walk Test (6MWT) trials, one with poles (WP) and the other without (NP). Gait characteristics and trunk measures in the sagittal and frontal planes were quantified using a 6 inertial sensor accelerometry system (APDM, Oregon, USA) as well as an eight camera 3-dimensional motion capture system (Vicon, Oxford, UK) with 2 force platforms (Kistler, Winterthur, Switzerland) embedded within. All variables were assessed using two-way repeated measures ANOVAs to compare NW to conventional walking and before and after the intervention. Results: When comparing walking WP to NP at initial pre-testing, significantly longer stride length, slower gait speed, and increased double support time were found to coincide with decreases in power generation and absorption at the hip and knee WP. However, following prolonged practice, a longer stride length, faster gait speed, and increased power generation at pre-swing at the hip and power absorption during loading and terminal swing about the knee were found WP post-intervention. Conclusions: An initial 8-week training period is necessary for novice NW in order to develop technique and to restore gait and postural alignment to more “normal” standards following training. Additionally, since the acquisition of the skill requires proper allocation of attention between two tasks: walking and pole manipulation, NW should be done so in a relatively safe environment, free of distraction and obstacles. Finally, with frail elderly, a longer acquisition period may be necessary since facilitation of movement must first occur.
Keywords: Nordic walking; Gait; Posture; Older Adults